A FUZZY METHOD ON DETERMINING OF JOB AND PERSONNEL EVALUATION RESULTS, AND MATCHING THEM WITH SUGGESTED MODEL - Ozdaban, Ismail; OZKAN, Coskun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
Human resources departments are the most important parts of an organization. Various organizational and managerial regulations use information from human resources. At this respect, it is essential for an organization to determine its current jobs and workers. In this research, personnel evaluation and job evaluation processes examined together, and a newer fuzzy distance measure formula was developed. Outputs of model were discussed, and some suggestions were given for further researches. According to results, it has been argued that educational needing, personnel requirements and job requirements of a company could be easily and economically determined with using of this method. Quality and quantity of educations, current and future statue of workers and jobs could be determined in model successfully.